Multilevel block factorization preconditioners : matrix-based analysis and algorithms for solving finite element equations - Vassilevski, Panayot S. (Springer, 2008)
This monograph is the first to provide a comprehensive, self-contained and rigorous presentation of some of the most powerful preconditioning methods for solving finite element equations in a common block-matrix factorization framework.